1984
DOI: 10.1042/bj2210189
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of collagen types synthesized by rabbit ear cartilage chondrocytes in vivo and in vitro

Abstract: This study compares the collagen types present in rabbit ear cartilage with those synthesized by dissociated chondrocytes in cell culture. The cartilage was first extracted with 4M-guanidinium chloride to remove proteoglycans. This step also extracted type I collagen. After pepsin solubilization of the residue, three additional, genetically distinct collagen types could be separated by fractional salt precipitation. On SDS (sodium dodecyl sulphate)/polyacrylamide-gel electrophoresis they were identified as typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Although the development of perichondrium-like regions in neocartilage constructs have been observed in relatively few previous studies-most notably by Yanaga and coworkers who also showed a spontaneous recapitulation of a perichondrium-like region after implantation, 46 the majority of elastic cartilage tissue engineering approaches tend to only utilize cells isolated from the cartilaginous region. 10,11,[47][48][49][50][51] The creation of engineered constructs possessing both cartilaginous and perichondrium regions, similar to that observed in native auricular cartilage, is of benefit toward the development of functional engineered constructs suitable for implantation. 2,10,44 The cartilaginous portion of the engineered constructs also appeared to be similar to that of native auricular cartilage with the presence of elastin, collagen types II and X, and sulfated proteoglycans.…”
Section: Discussionmentioning
confidence: 98%
“…Although the development of perichondrium-like regions in neocartilage constructs have been observed in relatively few previous studies-most notably by Yanaga and coworkers who also showed a spontaneous recapitulation of a perichondrium-like region after implantation, 46 the majority of elastic cartilage tissue engineering approaches tend to only utilize cells isolated from the cartilaginous region. 10,11,[47][48][49][50][51] The creation of engineered constructs possessing both cartilaginous and perichondrium regions, similar to that observed in native auricular cartilage, is of benefit toward the development of functional engineered constructs suitable for implantation. 2,10,44 The cartilaginous portion of the engineered constructs also appeared to be similar to that of native auricular cartilage with the presence of elastin, collagen types II and X, and sulfated proteoglycans.…”
Section: Discussionmentioning
confidence: 98%
“…During the GAG extraction process, acid-soluble collagen (mainly type I) was simultaneously extracted [9]. Samples were then digested with 1% (wt/vol) pepsin (Sigma) in 0.5 mol/L acetic acid (Fisher Scientific, Pittsburgh, PA) on an orbital shaker at 4°C for 24 hours.…”
Section: Extracellular Matrix Analysismentioning
confidence: 99%
“…Unfortunately, adequate proliferation of chondrocytes whilst maintaining their chondrogenic capacity has proven to be a challenge, as cells tend to dedifferentiate upon culturing [49]. Apart from growth factors and other soluble mediators, the biomechanical environment has proven to play an import role in cell behavior [50][51][52]. Different approaches to maintain cartilage phenotype have been proposed including growth factor mediation [53], coculturing [54] and 3D matrix culture environments [55].…”
Section: Chondrocytesmentioning
confidence: 99%